KAPASITAS MEMORI KERJA DALAM PEMECAHAN MASALAH MATEMATIKA - Anjariyah, Deka (Universitas Negeri Surabaya, 2019)
Abstract : Working memory capacity (WMC) is important for many cognitive processes including problem solving. This research compiles relevant literature about working memory capacity and problem solving, and discusses how working memory capacity can help or hinder people when trying to solve problems, especially mathematical problems. Working memory capacity plays a role in maintaining and retrieval of information in long-term memory (LTM), but under certain conditions, this can have an effect on the success of problem solving. Working memory capacity can support more effective problem solving by activating the retrieval and use of information that is relevant to the domain. On math problems about simple arithmetic for example, problem solvers with high working memory capacity can show differences from problem solvers with low working memory capacity. The source of this difference indicates superiority in coding or mathematical fact-taking or knowledge structures in LTM, the ability to deal with interference from relevant and irrelevant information, the ability to focus on problems, and the ability to produce or manipulate representations of mental problems. Keywords: Working memory capacity, problem solving, mathematical problems